Multifunctional and stable bone mimic proteinaceous matrix for bone tissue engineering. (July 2015) - Won, Jong-Eun; Yun, Ye-Rang; Jang, Jun-Hyeog; Yang, Sung-Hee; Kim, Joong-Hyun; Chrzanowski, Wojciech; Wall, Ivan B.; Knowles, Jonathan C.; Kim, Hae-Won
Abstract: Biomaterial surface design with biomimetic proteins holds great promise for successful regeneration of tissues including bone. Here we report a novel proteinaceous hybrid matrix mimicking bone extracellular matrix that has multifunctional capacity to promote stem cell adhesion and osteogenesis with excellent stability. Osteocalcin-fibronectin fusion protein holding collagen binding domain was networked with fibrillar collagen, featuring bone extracellular matrix mimic, to provide multifunctional and structurally-stable biomatrices. The hybrid protein, integrated homogeneously with collagen fibrillar networks, preserved structural stability over a month. Biological efficacy of the hybrid matrix was proven onto tethered surface of biopolymer porous scaffolds. Mesenchymal stem cells quickly anchored to the hybrid matrix, forming focal adhesions, and substantially conformed to cytoskeletal extensions, benefited from the fibronectin adhesive domains. Cells achieved high proliferative capacity to reach confluence rapidly and switched to a mature and osteogenic phenotype more effectively, resulting in greater osteogenic matrix syntheses and mineralization, driven by the engineered osteocalcin. The hybrid biomimetic matrix significantly improved in vivo bone formation in calvarial defects over 6 weeks. Based on the series of stimulated biological responses in vitro and in vivo the novel hybrid proteinaceous composition will be potentially useful as stem cell interfacing matrices for osteogenesis and bone regeneration.